Pemanfaatan Media Digital dalam Pembelajaran Pendidikan Agama Islam - Mohd Wiyono (Jurnal Pendidikan Islam Indonesia, 2025)
The utilization of digital media in Islamic Religious Education (IRE) learning is a response to the rapid development of information technology in the digital era. Digital media such as instructional videos, interactive applications, e-learning platforms, and social media have opened new opportunities for delivering religious content in a more engaging, flexible, and effective manner. This study aims to examine the forms of digital media utilization in IRE learning, the benefits it brings, and the challenges faced by educators and students. The method used is literature review and qualitative descriptive analysis. The findings indicate that digital media can enhance learning motivation, enrich learning resources, and facilitate contextual and collaborative learning. However, challenges such as limited access to technology, lack of digital literacy, and potential media misuse must also be considered. Therefore, appropriate pedagogical strategies and the strengthening of digital competencies among IRE teachers are needed to ensure that digital media usage is optimal and aligned with Islamic educational values.